PROBLEM ASPECTS AND PROSPECTS OF THE INNOVATIVE DEVELOPMENT OF THE ENTERPRISE UNDER THE CONDITIONS OF DIGITALIZATION (Development Service Industry Management, 2024)
The article focuses on issues of defining problems, as well as outlining prospects for innovative development of domestic enterprises. It is pointed out that the innovative development of business in Ukraine was not characterized by adequate stability even before the full-scale war, however, in the conditions of a critically high level of instability caused by the war, as the effect of disincentive factors increased, so did new difficulties and obstacles to the establishment and activation of innovative activities of domestic enterprises. Based on these principles, the purpose of the study is to identify problematic aspects and substantiate the prospects for ensuring the innovative development of domestic enterprises in the conditions of digitalization. It is argued that the main obstacles to the recovery and increase of innovative activity of enterprises in crisis conditions remain: difficulties in attracting investments, the high cost of attracting financial resources, the lack of qualified personnel, the "detachment" of education and science from real production, the lack of advanced technologies, the decline of the market intellectual property, etc. It has been proven that the prospects for the activation of innovative activities of domestic enterprises should be closely linked to the factors of digital transformation of the economy and society, as well as to the improvement of business management systems in the field of development and implementation of advanced technological innovations, development of innovative infrastructure, activation of cooperation programs with ICT entities, innovative technological ecosystem, educational institutions and research institutions. The impact of digitalization is constantly increasing and to which enterprises need to adapt qualitatively, which requires the development and implementation of new approaches to improving the management system, where the impact of digital transformation factors will be taken into account first of all. Digitalization and digitization technologies are being implemented on an ever larger scale and cover vital areas of business development and are critically important in the development of new types of activities. Solving the tasks of increasing the efficiency of providing digital technologies from the management of the enterprise requires improving the management system, which will be focused on identifying and assessing the impact of digitalization and digitization factors.
Keywords: management; enterprise management; innovative development; digital transformation; digitalization; digitization; enterprises; digital technologies; digital environment; material and technical support